The Effect of Central Metal Ions (Dy, Er, Ni, and V) on the Structural and HSA-Binding Properties of 2-Hydroxy-3-methoxybenzaldehyde Semicarbazone Complexes - Violeta Jevtovic; Jelena M. Živković; Aleksandra A. Rakić; Aljazi Abdullah Alrashidi; Maha Awjan Alreshidi; Elham A. Alzahrani; Odeh A. O. Alshammari; Mostafa Aly Hussien; Dušan Dimić (Inorganics)
2-Hydroxy-3-methoxybenzaldehyde semicarbazone (HMBS) is a multidentate ligand with interesting coordination behavior that depends on the central metal ion and the overall complex geometry. In this contribution, the structural characteristics of five HMBS-containing complexes with different metal ions (Dy, Er, Ni, and V) were investigated. Four binuclear and one mononuclear complex were selected from the Cambridge Structural Database. The crystallographic structures and intermolecular interactions in the solid state were analyzed, and the effect of central metal ions was elucidated. The different contributions of the most numerous contacts were explained by examining additional ligands in the structure. Density functional theory (DFT) optimizations were performed for the selected complexes, and the applicability of different computational methods was discussed. The Quantum Theory of Atoms in Molecules (QTAIMs) approach was employed to identify and quantify interactions in nickel and vanadium complexes, highlighting the role of weak intermolecular interactions between ligands in stabilizing the overall structure. Molecular docking studies of the interaction between these complexes and Human Serum Albumin (HSA) demonstrated that all compounds bind within the active pocket of the protein. The overall size and presence of aromatic rings emerged as key factors in the formation of stabilizing interactions.